2009
DOI: 10.1271/bbb.80601
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Skin-Whitening Effect of an Aqueous Extract ofSalicornia herbacea

Abstract: Salicornia herbacea (SH) is a halophyte that grows in the salt marshes along the coastline of South Korea, and is known to have antioxidative activity. In this study, the antioxidative and skin-whitening effects of SH aqueous extract were investigated in human dermal fibroblasts (HDFs) and B16 melanoma cells. The water extract of SH had potent antioxidative capacity and protected HDFs from tert-butyl hydroperoxide (tbOOH)-induced oxidative stress in a dose-dependent manner. In a cell cycle analysis, pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Arbutin, a structural analog of hydroquinone, can be metabolized into hydroquinone (Blaut et al, 2006), increasing the possibility of getting cancer. Thus, much research has identified tyrosinase inhibitors synthesized in the laboratory (Kubo et al, 2000;Shiino et al, 2001;Jun et al, 2007;Jirawattanapong et al, 2009;Delogu et al, 2010;Yi et al, 2010;Cha et al, 2011;Tajima et al, 2011;Song et al, 2012;Hamidian, 2013;Hamidian et al, 2013;Zhu et al, 2013) and extracted from plants (Piao et al, 2009;Sung et al, 2009;Chang et al, 2011;Liang et al, 2012;Zheng et al, 2012;Sarkhail et al, 2013). Some attention has been drawn to applying peptide sequences for tyrosinase inhibition; however, most of them are fragments isolated from known proteins and peptide-derived compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Arbutin, a structural analog of hydroquinone, can be metabolized into hydroquinone (Blaut et al, 2006), increasing the possibility of getting cancer. Thus, much research has identified tyrosinase inhibitors synthesized in the laboratory (Kubo et al, 2000;Shiino et al, 2001;Jun et al, 2007;Jirawattanapong et al, 2009;Delogu et al, 2010;Yi et al, 2010;Cha et al, 2011;Tajima et al, 2011;Song et al, 2012;Hamidian, 2013;Hamidian et al, 2013;Zhu et al, 2013) and extracted from plants (Piao et al, 2009;Sung et al, 2009;Chang et al, 2011;Liang et al, 2012;Zheng et al, 2012;Sarkhail et al, 2013). Some attention has been drawn to applying peptide sequences for tyrosinase inhibition; however, most of them are fragments isolated from known proteins and peptide-derived compounds.…”
Section: Introductionmentioning
confidence: 99%
“…S. herbacea is rich in natural minerals including Mg, Ca, Fe, K, dietary fibres (Tikhomirova, Ushakoya, Tikhomirov, Kalacheya, & Gros, 2008) and many bioactive substances, such as phytosterols (Zhu & Row, 2010), polysaccharides (Im et al, 2006) and phenolic compounds mainly flavonoids and phenolic acids (Kim, Yoon, & Cho, 2008;Kim et al, 2011;Lee, Lee, Shin, Kim, & Lee, 2004). This herb has been used as a food by coastal people and a folk medicine to treat a variety of diseases like gastroenteric disorders, diabetes, asthma, hepatitis, and cancer (Kang et al, 2011;Kong et al, 2008;Sung, Park, Seo, & Lee, 2009). Recent studies have shown that S. herbacea has antioxidative, anti-inflammatory, immunomodulatory, antimicrobial and antihyperlipidemic activities (Hwang et al, 2009;Kong et al, 2008;Park, Ko, Choi, & Chung, 2006;Sung et al, 2009) and described it as a promising source of functional foods and cosmetics (Kim, Choe, Choe, Lim, & Chay, 2007;Oh, Kim, Lee, Woo, & Choi, 2007;Zhu & Row, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular melanin release was measured as described previously, with slight modifications. 20,21) B16 cells were incubated at a density of 1 Â 10 5 cells in six-well plates overnight. -MSH (1 mm) or forskolin (20 mm) was then added, and the cells were treated with increasing concentrations of test substances in phenol red free DMEM for 5 d. Two hundred-mL aliquots of media were then transferred to 96-well plates and optical densities (OD) were measured at 400 nm using an ELISA reader.…”
Section: Methodsmentioning
confidence: 99%
“…Tyrosinase activities were determined as previously described. 20,21) Cells were cultured in six-well plates, incubated with A-Rh4 in phenol red free DMEM for 5 d, washed with ice-cold PBS, and lysed with phosphate buffer (pH 6.8) containing 1% Triton X-100. The cells were then disrupted by freeze-thawing, and lysate was clarified by centrifugation at 10;000 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%